2008
DOI: 10.1248/bpb.31.1199
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Ajuga decumbens on Osteoporosis and Arthritis

Abstract: Ajuga decumbens is a naturally occurring herb in Japan and China. The whole flowering plant of A. decumbens has been used in treatment of hypertension, hemoptysis, carbuncles and joint pain, etc.1,2) Many compounds have been isolated and identified from the whole plant, A. decumbens, [3][4][5][6][7] several of which show anti-tumor activity. 8) Recently, the number of cases of age related illnesses, e.g. osteoporosis and osteoarthritis have been trending upwards. These illnesses seriously affect people's daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…In the ADE diet group, the levels of PIICP increased markedly at week 8 compared with the placebo group. ADE has been reported to promote the repair of damaged cartilage (8) and enhance the synthesis of collagen in false aged model rats (7). Based on these findings, ADE may have enhanced the synthesis of collagen, especially type II collagen, in the subjects involved in the present study, as evidenced by the increase of PIICP, which is a type II collagen synthesis marker.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In the ADE diet group, the levels of PIICP increased markedly at week 8 compared with the placebo group. ADE has been reported to promote the repair of damaged cartilage (8) and enhance the synthesis of collagen in false aged model rats (7). Based on these findings, ADE may have enhanced the synthesis of collagen, especially type II collagen, in the subjects involved in the present study, as evidenced by the increase of PIICP, which is a type II collagen synthesis marker.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, the levels of MMP-13 were significantly reduced in both groups compared with the baseline; however the changes of MMP-13 levels from baseline were more substantially reduced at weeks 4, 8 and 12 in the ADE diet group compared with the placebo group, although the difference was not significant. It has been reported that MMP-13 may be induced by inflammatory cytokines (18), whereas ADE exhibits an anti-inflammatory action on an arthritis model (7). Therefore, the anti-inflammatory action of ADE may be associated with the suppression of MMP-13.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Additionally, Ajuga has been used in Iranian traditional medicine for the treatment of joint pain, gout, and jaundice [7]. All plants of A. decumbens have been utilized as a kind of folk medicine for a long time in China and Japan owing to their antibacterial, antiinflammatory, antitumor and antiviral activities [8][9][10][11]. Many compounds whose structures have been characterized were isolated from A.…”
Section: Introductionmentioning
confidence: 99%